2015
DOI: 10.2196/jmir.4950
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an eHealth Portal on Health Care Professionals’ Interaction with Patients: Qualitative Study

Abstract: BackgroundPeople who undergo weight loss surgery require a comprehensive treatment program to achieve successful outcomes. eHealth solutions, such as secure online portals, create new opportunities for improved health care delivery and care, but depend on the organizational delivery systems and on the health care professionals providing it. So far, these have received limited attention and the overall adoption of eHealth solutions remains low. In this study, a secure eHealth portal was implemented in a bariatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(88 citation statements)
references
References 48 publications
(50 reference statements)
0
84
0
4
Order By: Relevance
“…However, it is also important to measure the acceptability of such strategies, and whether they improve MBS outcomes. Indeed, Das et al 13 reported that an eHealth portal tailored to provide postoperative MBS support decreased attrition rates in clinical follow-ups and improved adult patients' health. Additionally, the eHealth portal became a safe outlet where patients could express their concerns and seek assistance in real-time.…”
Section: Ehealth Strategies Applied To Diabetes Managementmentioning
confidence: 99%
“…However, it is also important to measure the acceptability of such strategies, and whether they improve MBS outcomes. Indeed, Das et al 13 reported that an eHealth portal tailored to provide postoperative MBS support decreased attrition rates in clinical follow-ups and improved adult patients' health. Additionally, the eHealth portal became a safe outlet where patients could express their concerns and seek assistance in real-time.…”
Section: Ehealth Strategies Applied To Diabetes Managementmentioning
confidence: 99%
“…Optimal methods for information delivery to cancer survivors are not clear. Patients in rural areas have expressed a preference for electronic formats for ongoing contact but there is little evidence informing optimal delivery mechanisms and there are organizational challenges with electronic communication of health care . Newer technologies, such as mobile phones, have been rapidly adopted with 77% of American adults owning a smartphone, up from 35% in 2011 .…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review (Ye et al, 2010) shows that the use of e-mail in patient-provider communication has the potential to improve health communication between patients and providers, thus increasing satisfaction and the quality of care. Other studies reveal that electronic communication between healthcare professionals and patients can improve patient-centred care (Cornwall, Moore, & Plant, 2008), facilitate patient information (Kinnane, Milne, Kinnane, & Milne, 2010), prevent dropout and deterioration of patients' health (Das, Faxvaag, & Svanaes, 2015). However, eHealth interventions for people with type 2 diabetes appear to vary widely in terms of follow-up, length and quality (Pal et al, 2013).…”
Section: Backg Rou N Dmentioning
confidence: 99%